Co-pigmentation of sweet potato and greater yam anthocyanins with selected phenolic acids and its effect on in vitro antioxidant activity - A N Jyothi; V.R. Vishnu; A. Abhishek (JOURNAL OF ROOT CROPS, 2024)
The effect of co-pigmentation on the antioxidant capacity of anthocyanins isolated from purple colored root tubers of greater yam (Dioscorea alata, Acc. Da-340) and sweet potato (Ipomoea batatas, cv Bhu Krishna) with caffeic, ferulic and p-coumaric acids was investigated in this study. The DPPH radical scavenging activity of both the anthocyanins enhanced significantly after co-pigmentation. However, phenolic acids behaved differently with different concentrations of anthocyanins. Except at very low anthocyanin concentrations, caffeic acid and ferulic acid served as effective co-pigments for greater yam and sweet potato anthocyanins respectively, leading to an increase in antioxidant potential. At very low concentrations of the pigment and co-pigment used, the effect was reverse. The highest % radical scavenging activity was observed for greater yam anthocyanins at a concentration of 6 ?gml-1 and 26 ?g ml-1 of ferulic acid as the co-pigment, followed by the same concentration of anthocyanins and 24 ?g ml-1 of caffeic acid. P-coumaric acid was not as effective as caffeic and ferulic acids. This study indicated the existence of some distinct intermolecular interactions that ensue in the complex framework of natural colors and the results could beuseful in designing bioactive food colorants.